Identidad y prácticas rituales funerarias en Costa Rica, 300-800 d.C. Una interpretación. - Peytrequín Gómez, Jeffrey (2012)
Curridabat Phase (300-800 A.D.) funerary practices, on Central Highlands of Costa Rica, could objective certain social integration principles. The funerary-ritual material culture served as an active cosmological messages transmission medium. These messages were understood by the mourners and reinforced their group identity. Both the ritual action and the mortuary arrangement were constituted as much in (1) the arena for the identity negotiation of the alive as of dead ones; (2) an update of the beliefs (origin myths) through the ceremony, and (3) the symbolic representation of the social structure.